2015
DOI: 10.1073/pnas.1502670112
|View full text |Cite
|
Sign up to set email alerts
|

Conditional steroidogenic cell-targeted deletion of TSPO unveils a crucial role in viability and hormone-dependent steroid formation

Abstract: Translocator protein (TSPO) is a key member of the mitochondrial cholesterol transport complex in steroidogenic tissues. To assess the function of TSPO, we generated two lines of Cre-mediated Tspo conditional knockout (cKO) mice. First, gonadal somatic celltargeting Amhr2-Cre mice were crossed with Tspo-floxed mice to obtain F1 Tspo Amhr2 cKO mice (Tspo fl/fl ;Amhr2-Cre /+). The unexpected Mendelian ratio of 4.4% cKO mice was confirmed by genotyping of 12.5-day-postcoitum (dpc) embryos. As Amhr2-Cre is express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
112
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(120 citation statements)
references
References 45 publications
7
112
1
Order By: Relevance
“…These studies not only question the role TSPO holds in steroidogenesis but contrast early attempts to generate Tspo -/-knockout mice, which resulted in embryonic lethality (5). However, the viability of mice has been shown to vary depending on methodology: Nr5a1-driven conditional knock-outs were born at a normal Mendelian ratio while Amhr2-Cre driven conditional knock-outs were born at a ratio of 4.4% (111). Global Tspo knockout phenotypes can range from lethal, when whole gene deletion is performed, to no phenotype, as in the case of cre-loxP technique, thus presenting the possibility that methodological differences may be the cause of such discrepancy (112).…”
Section: Tspo -/-Knockout Mice: New Insights Of An Old Functionmentioning
confidence: 99%
See 2 more Smart Citations
“…These studies not only question the role TSPO holds in steroidogenesis but contrast early attempts to generate Tspo -/-knockout mice, which resulted in embryonic lethality (5). However, the viability of mice has been shown to vary depending on methodology: Nr5a1-driven conditional knock-outs were born at a normal Mendelian ratio while Amhr2-Cre driven conditional knock-outs were born at a ratio of 4.4% (111). Global Tspo knockout phenotypes can range from lethal, when whole gene deletion is performed, to no phenotype, as in the case of cre-loxP technique, thus presenting the possibility that methodological differences may be the cause of such discrepancy (112).…”
Section: Tspo -/-Knockout Mice: New Insights Of An Old Functionmentioning
confidence: 99%
“…Recently, however, a number of studies from independent groups have reported that TSPO global knock out mice are viable and that loss of the protein has no effect on basal steroid hormone biosynthesis (32,35,110,111). These studies not only question the role TSPO holds in steroidogenesis but contrast early attempts to generate Tspo -/-knockout mice, which resulted in embryonic lethality (5).…”
Section: Tspo -/-Knockout Mice: New Insights Of An Old Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…The initial and ratelimiting step involves the transport of cholesterol from the outer to the inner mitochondrial membrane by steroidogenic acute regulatory protein (StAR, encoded by STAR) (23,306). Evidence from recent studies in mice has raised the possibility that StAR works in conjunction with other proteins, including translocator protein (TSPO), to facilitate this shuttling process (141). At the inner mitochondrial membrane, cholesterol is converted to pregnenolone by the cholesterol side chain cleavage enzyme (P450scc, encoded by CYP11A1) (468).…”
Section: A Aldosterone Synthesismentioning
confidence: 99%
“…Due to Tspo sequence conservation from bacteria to humans, there has been some interest in studying the functional evolution of this gene (Fan et al 2012). TSPO2 (PBRL/Peripheral benzodiazepam-like) was identified as a gene that emerged from a duplication event preceding speciation of reptiles, birds and mammals (Nakazawa et al 2009).…”
Section: Is Tspo2 An Isofunctional or Heterofunctional Homolog?mentioning
confidence: 99%